Experiences on the quality of education assessment in a network engineering program in Lima city - Nieto Chaupis, Huber (2017)
We have tested a scheme that measures the quality of education (QoE) in the network engineering program through the progress, outcomes or any evidence of the capstone project. We use simple relations based on efficiencies but weighted and with ambiguities. For this end, the performance of students are quantified through the definition of events which are actions that can help weakly or substantially to the progress of the project. In this manner students were suggested to use the following topics in the capstone: (i) Telecommunications, (ii) Basic Sciences and (iii) Programming, in their individual projects. The resulting statistics of the QoE was of order of 62% fact which is interpreted in the sense that one of three of the expected bachelors of engineering has not consolidated its knowledge in the courses with a poor correlation in conjunction to the topics of telecommunications.